Behavioural factors associated with successful weight loss and maintenance - Joachim Westenhöfer and Astrid Stellfeldt and W. Martens and B. Nommensen (1998)
[in International Journal of Obesity and Related Metabolic Disorders, 22 (Suppl. 3), S.287]